Optimal Timing of Endoscopic Intervention for Acute Variceal Bleeding in Cirrhotic Patients: A Systematic Review and Meta-Analysis - Jiang, Yang; Lu, Yandi; Wang, Yang (Turkish Journal of Gastroenterology, 2025)
Background: Acute variceal bleeding (AVB) is a severe complication in cirrhotic patients. The optimal timing for endoscopic treatment remains uncertain. Methods: A systematic search of PubMed, Embase, and the Cochrane Library was conducted. Outcomes included mortality, rebleeding rate, number of red blood cells (RBC) transfused, length of hospitalization, and other clinical endpoints. Study quality was assessed using the Newcastle–Ottawa Scale (NOS). Meta-analysis was performed using RevMan 5.4.1 (Cochrane, Oxford, United Kingdom) and Stata 18.0 (StataCorp LLC, College Station, United States), with subgroup, sensitivity, and publication bias analyses. Results: No significant differences were observed between early and delayed endoscopy groups for the outcomes. However, in-hospital mortality was higher in the early endoscopy group (odds ratio (OR) = 1.55, 95% CI: 0.92-2.61, P = .10) and reached significance in sensi tivity analysis (OR = 1.76, 95% CI: 1.02-3.04, P = .04). Additionally, the early group tended to reduce the 6-week bleeding rate (OR = 0.78; 95% CI: 0.49-1.33; P = .4) and reached significance in sensitivity analysis (OR = 0.63, 95% CI: 0.43-0.92, P = .02). Moreover, the early group tended to require fewer RBC transfusions (mean difference (MD) = −0.62, 95% CI: −1.33 to 0.09, P = .09), confirmed in subgroup analysis (MD = −1.32, 95% CI: −2.41 to −0.24, P = .02). Conclusion: No significant differences were found between groups for outcomes. However, subgroup or sensitivity analysis revealed that early endoscopy may increase in-hospital mortality, while reducing 6-week rebleeding and RBC transfusion. Further randomized trials are needed to confirm these findings. Cite this article as: Jiang Y, Lu Y, Wang Y. Optimal timing of endoscopic intervention for acute variceal bleeding in cirrhotic patients: A systematic review and meta-analysis. Turk J Gastroenterol. Published online November 21, 2025. doi:10.5152/tjg.2025.25432.